Immunoproteasome inhibition reduces donor specific antibody production and cardiac allograft vasculopathy in a mouse heart transplantation model - Schwalb, Allison M.; Anwar, Imran; DeLaura, Isabel; Ladowski, Joseph M.; Yoon, Janghoon; Belloni, Rafaela; Song, Mingqing; Glass, Carolyn; Wang, Jun; Knechtle, Stuart; Kwun, Jean (Frontiers in Transplantation, 2024)
ObjectiveCardiac Allograft Vasculopathy (CAV), a process of vascular damage accelerated by antibody-mediated rejection (AMR), is one of the leading causes of cardiac transplant failure. Proteasome inhibitors (PIs) are utilized to treat AMR, however PI-associated toxicity limits their therapeutic utility. Novel immunoproteasome inhibitors (IPIs) have higher specificity for immune cells and have not been investigated for AMR in cardiac transplant patients. We sought to evaluate IPI effect on AMR in a murine cardiac transplant model.MethodsFully MHC mismatched C57BL/6 to huCD52Tg heterotopic heart transplantations were performed. Recipients were treated with alemtuzumab (10 µg, IP) on days −2, −1, 2, and 4 and anti-CD25mAb (PC61, 100 µg, IP) on day 7 to accelerate AMR with or without IPI (ONX-0914,15 mg/kg, SQ), administered on transplant day and three times a week thereafter.ResultsAnimals without IPI gradually developed post-transplant donor-specific antibody (DSA) and showed a significantly elevated DSA level compared to animals receiving IPI. (TFXM 48.86 vs. 14.17; p = 0.0291, BFXM 43.53 vs. 6.114; p = 0.0031). Accordingly, H&E staining of allograft showed reduced evidence of AMR with IPI compared to controls (P = 0.0410). Notably, increased mortality was observed in the IPI treated group.ConclusionThis study demonstrated the ability of ONYX-0914, an IPI, to control post-transplant DSA production and the AMR development in a heart transplant model. However, IPI-resistant DSA production was also observed and increased mortality with IPI therapy raises concerns about potential toxicity. Further investigation is warranted to assess the utility and potential risk associated with the use of IPI as a post-transplant maintenance immunosuppression.